Delegating for results - Maddux, Robert B. (Crisp Pub. Menlo ParkUS, 1998)
Offers basic principles for analysing the process of delegation. Includes guidelines for selecting the right person; preparing staff for delegation; and using delegation as a tool for managing change. Provides exercises and worksheets which readers can use to evaluate current delegation skills; identify problem areas; and find solutions.